Napoleon : the end of glory - Price, Munro (Oxford University Press, 2014)
On April 20, 1814, after a dizzying series of battles, campaigns, and diplomatic intrigues, a defeated Napoleon Bonaparte made his farewell speech to the Old Guard in the courtyard of the Chateau de Fontainebleau and set off for exile on the island of Elba. Napoleonic legend asserts that the Emperor was brought down by foreign powers determined to destroy him and discredit his achievements, with the aid of highly placed domestic traitors. Others argue that once Napoleon's military defeats began in 1812, his fall became inevitable. But in fact, as Munro Price shows in this brilliant new book, N.